FAKTOR YANG MEMPENGARUHI KEPUTUSAN PENGGUNAAN JASA LAUNDRY BANDAR LAMPUNG - BIMO GONDO KUSUMO; Nur Efendi; Prasetya Nugraha (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2022)
This study aims to determine the effect of price, promotion, and process on the decision to use Plaza Laundry services in Bandar Lampung. This type of research is quantitative with an explanatory approach. The population in this study were all members of Plaza Laundry. The sampling technique used is simple random sampling with a sample of 58 respondents. The data was obtained from a questionnaire using a Likert scale. The data analysis of this research used multiple linear regression analysis. The results of the study partially explain that the price has a positive and significant effect on the decision to use services. The promotion has a positive and significant effect on service use. The process has a positive and significant effect on the use of services. Simultaneously, price, promotion, and process have a positive and significant effect on the decision to use services. The implication of this research is that Plaza Laundry should gradually start providing innovations related to the promotion of service products so that the reach of consumers becomes wider. Key Words: Service Usage Decisions, Price, Promotion, Process